KEKUATAN HUKUM KARTU BPJS KESEHATAN DALAM PENDAFTARAN PERALIHAN HAK ATAS TANAH - Diyan Isnaeni (Jurnal Hukum dan Kenotariatan, 2022)
Since March 1, 2022, the requirements for registration services for the transfer of land rights due to sale and purchase must be accompanied by a photocopy of the BPJS Health Card with the issuance of the Director General of PHPT of the Ministry of ATR/BPN Number: HR 02/153-400/II/2022, as a follow-up to the Presidential Instruction Republic of Indonesia Number 1 of 2022 concerning Optimizing the Implementation of the National Health Insurance Program, land buyers must have registered with the Indonesian government's health insurance program and are active participants.There is legal uncertainty for people who want to register the transfer of rights due to buying and selling with the issuance of the Director General of PHPT ATR/BPN No. HR.02/153-400/II/2022, especially the 2 (two) and 3 (three) numbers. Juridically normative Letter of the Director General of PHPT ATR/BPN No.HR.02/153-400/II/2022, especially number 3 (three) does not have strong legal force, and as a result of the law the requirements for a BPJS Health card are not binding for someone who wants to apply application for registration of the exercise of rights even though it is not equipped with a BPJS Health Card. However, implementing it has strong legal force because the product from the registration of the transfer of rights due to sale and purchase in the form of a land title certificate cannot be taken if it is not equipped with a BPJS Card because it is not yet a BPJS Health participant. Keywords: Registration of Transfer of Rights, BPJS Health, Legal Force                                                                           ABSTRAKSejak 1 Maret Tahun 2022 syarat permohonan pelayanan pendaftaran peralihan hak atas tanah  karena jual beli harus dilengkapi dengan fotocopy Kartu BPJS Kesehatan dengan dikeluarkannya Surat Dirjen PHPT Kementrian ATR/BPN Nomor: HR 02/153-400/II/2022, Sebagai tindak lanjut Instruksi Presiden Republik Indonesia Nomor 1 Tahun 2022 tentang Optimalisasi Pelaksanaan Program Jaminan Kesehatan Nasional, pembeli tanah harus sudah terdaftar jaminan kesehatan program pemerintah Indonesia dan merupakan peserta aktif.Ada ketidakpastian hukum bagi masyarakat yang ingin mendaftarkan peralihan hak karena jual beli dengan diterbitkannya  Surat Dirjen PHPT ATR/BPN No.HR.02/153-400/II/2022 khususnya angka ke 2 (dua) dan ke ke 3 (tiga). Secara yuridis normatif Surat Dirjen PHPT ATR/BPN No.HR.02/153-400/II/2022 khususnya  angka ke 3 (tiga) tidak mempunyai kekuatan hukum yang kuat, dan akibat hukumnya syarat kartu BPJS Kesehatan tidak mengikat bagi seseorang yang ingin mengajukan permohonan pendaftaran perlaihan hak walaupun tidak dilengkapi dengan Kartu BPJS Kesehatan. Tetapi secara implementif  mempunyai kekuatan hukum yang kuat karena produk dari pendaftaran peralihan hak karena jual beli berupa sertifikat hak atas tanah belum bisa diambil apabila tidak dilengkapi dengan Kartu BPJS karena belum sebagai peserta BPJS Kesehatan. Kunci: Perndaftaran Peralihan Hak, BPJS Kesehatan, Kekuatan Hukum